2021
DOI: 10.18805/ag.d-5321
|View full text |Cite
|
Sign up to set email alerts
|

​Efficiency of Biocomposted Agroindustrial Wastes and Their Response in the Growth and Yield of Vigna unguiculata (L.) Walp

Abstract: Background: Agroindustrial by-products of cocoa shell and jack fruit peels generally considered as organic waste have almost no economic value and create a big problem in disposal time. A significant amount of biocomposted cocoa shell and jack fruit peel waste is used as organic manure that enhances growth in Vigna unguiculata (L.) Walp. Methods: This research work was conducted in the period of 2019 in the Department of Botany, Avinashilingam Institute for Home Science and Higher Education for Women, Coimbato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…The present results also coincide with the previous findings that integration of NPK (50%) + FYM (50%) +biofertilizers had significant positive impact on yield per plant (1149 g) and total yield (11.05 t ha -1 ) of king chilli Effect of Vermicomposted Vegetable and Fruit Wastes on the Vegetative and Yield Parameters of Lablab [Lablab Purpureus (L.)... (Vimera et al, 2012) and in pigeon pea where an increase in weight of pod, number of pods/plants (243 g and 400 g) were noted when poultry manure was used (Birajdar et al, 2018). Similar results were observed by Silpa and Vijayalakshmi (2021).…”
Section: Yield Parameterssupporting
confidence: 91%
“…The present results also coincide with the previous findings that integration of NPK (50%) + FYM (50%) +biofertilizers had significant positive impact on yield per plant (1149 g) and total yield (11.05 t ha -1 ) of king chilli Effect of Vermicomposted Vegetable and Fruit Wastes on the Vegetative and Yield Parameters of Lablab [Lablab Purpureus (L.)... (Vimera et al, 2012) and in pigeon pea where an increase in weight of pod, number of pods/plants (243 g and 400 g) were noted when poultry manure was used (Birajdar et al, 2018). Similar results were observed by Silpa and Vijayalakshmi (2021).…”
Section: Yield Parameterssupporting
confidence: 91%
“…El-Mohamedy et al (2015) A significant increase in plant height, number of leaves, number of branches, fresh weight and dry weight was observed in bio-compost when compared to the control in potato (Solanum tuberosum L.) plants. The results coincides with Silpa and Vijayalakshmi (2022) who confirmed that the application of biocomposted cocoa shell and jack fruit peel waste increased the shoot length (175.83 cm), The present study was also in agreement where an increase in plant height (32.56 cm) was noted with the application of T 3 -Azolla vermicompost supplemented with 50% NPK, was observed Palia et al (2021).…”
Section: Biometric Characterssupporting
confidence: 92%
“…Similar results were observed by Silpa and Vijayalakshmi, (2021) with the inclusion of Jackfruit peel vermicompost resulted in the highest yield of Vigna unguiculata(L) Walp in the treatment 8 such as number of pods (21), length of the pod (16.50 cm), weight of the seeds (1.68 g), pod fresh weight (5.711 g) and dry weight (2.398 g). The results of this particular study also is similar to that of Hasan et al,(2021) with the application of N and P fertilizer on Groundnut plants and found that the plant height (20.65) increased along with the number of pods 74.28% in treatment 15.…”
Section: Fresh Weight and Dry Weightsupporting
confidence: 81%